Kerentanan Human Security Pekerja Migran Indonesia terhadap Human Trafficking dalam Sistem Perekrutan Digital di Arab Saudi: Analisis Kelemahan Regulasi - Salsa Kurnia Syahbani (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
The digitalization of labor recruitment systems has fundamentally transformed the migration pathways for Indonesian migrant workers (PMI), particularly those destined for Saudi Arabia. While digital platforms including online portals, social media, and mobile applications promise efficiency and broader access to overseas employment opportunities, they have simultaneously created new and complex vulnerabilities that expose workers to human trafficking. This study employs a qualitative approach using document analysis and systematic literature review to examine how weaknesses in Indonesia's regulatory framework fail to adequately protect PMI at the recruitment stage. Drawing on the human security framework particularly the dimensions of personal security and economic security as articulated in the UNDP 1994 Human Development Report. This article argues that the Indonesian government's inability to effectively monitor and regulate digital recruitment actors constitutes a critical governance failure that enables traffickers to exploit prospective migrant workers. Key findings reveal three intersecting vulnerabilities: (1) the proliferation of unregulated digital recruitment intermediaries operating outside formal licensing frameworks; (2) insufficient legal enforcement mechanisms against fraudulent digital job advertisements targeting economically vulnerable communities; and (3) the structural compounding of digital recruitment vulnerabilities with destination-country risks, particularly the kafala sponsorship system in Saudi Arabia.